Leaking stoppage composition, leaking stoppage material and application of leaking stoppage material

CN119677825AActive Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380054862.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-08-24
Publication Date
2025-03-21
Estimated Expiration
2043-08-24

AI Technical Summary

Technical Problem

Existing leakage plugging compositions perform poorly in terms of erosion resistance, high temperature resistance and compressive strength, making it difficult to effectively plug leakage in formations containing flowing water.

Method used

Provides a leak plugging composition that can be cross-linked to form a gel before being injected into the formation or during the injection process. The mass retention rate of the gel when washed for 30 minutes at a water flow rate of 10 m/min under conditions of 50-180°C is: More than 90%, the formed leak-proof material has a lap shear strength of 0.1-0.14MPa and a compressive strength of not less than 16MPa.

Benefits of technology

It achieves effective plugging in formations containing flowing water. The plugging material can stay strongly around the wellbore and has significantly improved resistance to water dilution and high temperature resistance. It is suitable for water-bearing formations of 50-180°C.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of petroleum drilling, and discloses a leaking stoppage composition, a leaking stoppage material and application of the leaking stoppage composition and the leaking stoppage material. The plugging composition can be cross-linked to form gel before being injected into a stratum or in the process of being injected into the stratum, the gel can be cured at a leakage stratum to form the plugging material, and the mass retention rate of the gel after being washed for 30 min at the water flow speed of 10 m / min under the condition of 50-180 DEG C is 90% or above; the lap joint anti-shearing strength of the plugging material is 0.1 to 0.14 MPa. The invention further discloses a preparation method of the plugging material. The plugging composition is suitable for water-containing stratums with the temperature not higher than 180 DEG C, especially stratums containing flowing water. The plugging composition disclosed by the invention can be cross-linked to form gel, can strongly reside around a borehole after being injected into a water-containing stratum, and can be cured under a stratum condition to form a plugging material to finally plug a leakage layer. The plugging material disclosed by the invention is remarkably improved in the aspects of water dilution resistance, interface bonding strength, high temperature resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Lost-circulation plugging composition and lost-circulation plugging material and their application

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Chinese patent applications No. 202211082422.9, 202211082409.3 and 202211082427.1 filed on September 6, 2022, the contents of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to the technical field of oil drilling, in particular to a plugging composition and a plugging material and applications thereof. Background Art

[0004] Water-bearing leakage zones are usually connected to underground rivers, and the groundwater is very active. The resulting well leakage is fast and the loss volume is large, which is often difficult to deal with. There is currently no particularly good solution to the problem of plugging water-bearing leakage zones. This is mainly because the plugging slurry is easily diluted or moved with the water flow. The direct results are: (1) dilution reduces the viscosity of the plugging slurry and the concentration of the plugging material. It is easy to flow away under the action of pressure and is difficult to accumulate near the entrance of the leakage zone; (2) for the consolidation plugging slurry, the plugging slurry is difficult to solidify after dilution, or the coagulation strength is greatly reduced, making it difficult to support the destructive effect of the slurry, resulting in plugging failure; (3) If the formation water is flowing water, the plugging slurry will be quickly carried away by the formation water under the action of the water flow, and it will not form a sealing wall, resulting in plugging failure. The plugging of water-bearing formations, especially those containing flowing water, has not been well solved.

[0005] CN111849437A relates to a pretreatment agent for plugging leaks in water-bearing formations in the field of oil drilling, as well as its preparation method and application. The pretreatment agent for plugging leaks in water-bearing formations comprises the following components, by weight: 100 parts of a water-soluble phenolic formaldehyde, 0.110 parts of a water-soluble phenolic emulsifier, and 10-400 parts of water. However, this pretreatment agent only forms a highly adhesive and wall-clinging substance in water layers and is easily washed away by water when applied to formations containing flowing water.

[0006] In view of this, there is an urgent need to develop a plugging composition suitable for flowing water formations that has excellent performance in terms of anti-thinning, retention, high temperature resistance and compressive strength.

[0007] Summary of the Invention

[0008] The purpose of the present invention is to overcome the problems of poor performance of the plugging composition in the prior art in terms of resistance to dilution, high temperature resistance and compressive strength, and to provide a plugging composition and a plugging material and their application. The plugging composition is suitable for application in formations containing flowing water.

[0009] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a plugging composition, which can be cross-linked to form a gel before or during injection into the formation, and the gel can be solidified at the leakage formation to form a plugging material, wherein the mass retention rate of the gel after being flushed for 30 minutes at a water flow rate of 10m / min at 50-180°C is above 90%; the lap shear strength of the plugging material is 0.1-0.14MPa.

[0010] A second aspect of the present invention provides a plugging material, which is obtained by curing the aforementioned plugging composition.

[0011] The third aspect of the present invention provides the use of the aforementioned plugging composition or the aforementioned plugging material in plugging oil well formations; preferably, the oil well formation is an oil well formation containing flowing water at a temperature of 50-180°C.

[0012] A fourth aspect of the present invention provides an oil well plugging method, which includes directly injecting the aforementioned plugging composition into the cracks in the oil well formation so that the plugging composition undergoes cross-linking to form a gel during the injection process into the formation, or injecting the aforementioned plugging composition into the cracks in the oil well formation after forming a gel, wherein under formation conditions, the gel solidifies at the leaking formation to form a plugging material; wherein the mass retention rate of the gel after being flushed at a water flow rate of 10 m / min for 30 minutes at 50-180°C is above 90%; and the lap shear strength of the plugging material is 0.1-0.14 MPa.

[0013] The aforementioned plugging composition or the aforementioned plugging material is used in the process of leakage in a flowing water-containing formation; in particular, in the process of leakage in a flowing water-containing formation at 50-180°C.

[0014] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0015] (1) The plugging composition of the present invention can be cross-linked to form a gel before or during injection into the formation, and the gel can be solidified at the leaking formation to form a plugging material. The mass retention rate of the gel after flushing for 30 minutes at a water flow rate of 10 m / min at 50-180°C is above 90%. After being injected into the water-bearing formation, it can strongly reside around the wellbore and can be solidified under the formation conditions to generate a plugging material with a lap shear strength of 0.1-0.14 MPa and a compressive strength of not less than 16 MPa, thereby ultimately plugging the leaking formation.

[0016] (2) The cross-linkable polymer in the plugging composition of the present invention first undergoes a cross-linking reaction with the cross-linking agent to form a gel, which encapsulates the other components in the network structure formed by the cross-linking, so that the system will not be dispersed by water. The mass retention rate after 10 m / min water flow for 30 minutes is above 90%, and the compressive strength can reach 7 MPa.

[0017] (3) Compared with existing plugging compositions, the plugging material formed by the plugging composition of the present invention has significant improvements in resistance to water dilution and high temperature, and can be used for plugging water-containing formations, especially those containing flowing water at 50-180°C. DETAILED DESCRIPTION

[0018] The endpoints of the ranges and any values ​​disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.

[0019] The first aspect of the present invention provides a plugging composition, which can be cross-linked to form a gel before or during injection into the formation, and the gel can be solidified at the leaking formation to form a plugging material, wherein the mass retention rate of the gel after being flushed at a water flow rate of 10m / min for 30min at 50-180°C is above 90%; the lap shear strength of the plugging material is 0.1-0.14MPa.

[0020] In the present invention, the consistency of the system is tested using a pressurized viscometer OWC-9380B under the following test conditions: temperature 100-180°C and pressure 20-100 MPa. The plugging composition has a consistency of <20 BC, a consistency of 30-40 BC indicates a gel state, and a consistency of >70 BC indicates a fully cured plugging material.

[0021] In the present invention, when the test temperature is below 100°C, the gel stage and the fully cured stage can also be determined by the viscosity value. The instrument used for the viscosity is a Brookfield viscometer DV-2, a rotor of No. 61-65, and a speed of 1000s. -1 After mixing the plugging composition, place it in a set temperature environment (for example, the temperature corresponding to the formation), and use a viscometer to measure the viscosity at regular intervals. The time point when the viscosity value increases is recorded as the time of gel formation. Continue to measure. When the viscosity value stabilizes and no longer increases, it means that it has reached complete solidification, which is recorded as the time of complete solidification.

[0022] In the present invention, the mass retention rate of the gel after scouring with water at a flow rate of 10 m / min for 30 minutes is greater than 90%, for example, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or any value within a range consisting of any two of the above values, preferably 93-97%. The lap shear strength of the plugging material is 0.1-0.14 MPa, for example, 0.1 MPa, 0.11 MPa, 0.12 MPa, 0.13 MPa, 0.14 MPa, or any value within a range consisting of any two of the above values.

[0023] In the present invention, the lap shear strength of the plugging material refers to the lap shear strength at the interface between the plugging material and the rock. A higher lap shear strength indicates a greater lap shear strength at the interface between the plugging material and the rock, and a less likely the plugging material will separate from the rock interface.

[0024] In the present invention, the mass retention rate can reflect the water-resistance and thinning resistance. The higher the mass retention rate, the better the water-resistance and thinning resistance, and vice versa.

[0025] In the present invention, the mass retention rate is measured using the simulation device for plugging water-bearing loss zones disclosed in CN113123756A. The formed gel is allowed to stand for 30 minutes. 500 mL of the gel is then injected into the testing device under water flow (for details, see CN113123756A, "Simulation device for plugging water-bearing loss zones"). The water flow rate is set at 10 m / min, and the gel injection rate is set at 20 m / min. After gel injection, water injection is continued for 30 minutes. The sample is then removed and the mass retention rate is calculated. Mass retention rate = post-flushing sample mass / injected gel mass * 100%.

[0026] In some embodiments of the present invention, the compressive strength of the plugging material is not less than 7 MPa, for example, 7 MPa, 8 MPa, 9 MPa, 10 MPa, 11 MPa, 12 MPa, and any value in the range of any two of the above values, preferably 8-10 MPa.

[0027] In the present invention, the bearing strength is tested by using the simulation device for plugging water-bearing leakage layers disclosed in CN113123756A. The maximum pressure of the pressure gauge 17 is read as the bearing strength of the plugging material.

[0028] In some embodiments of the present invention, the compressive strength of the plugging material is not less than 16 MPa, preferably 18-25 MPa.

[0029] In some embodiments of the present invention, the lost circulation formation is a water-bearing formation, preferably a formation containing flowing water.

[0030] In the present invention, the leakage formation is a leakage wellbore.

[0031] In some embodiments of the present invention, the temperature of the leakage formation is 50-180°C.

[0032] In some embodiments of the present invention, the plugging composition comprises the following components: a cross-linkable polymer, a cross-linking agent, a strengthening agent, and a solvent; wherein the cross-linking agent comprises a metal cross-linking agent and / or an allyl cross-linking agent, and the strengthening agent is strengthening agent I and / or strengthening agent II;

[0033] The enhancer I comprises a monomer represented by formula (I), dopamine and an initiator;

[0034] Among them, R1, R2, R 21 、R 22 、R 31 and R 32 Each independently is hydrogen or C1-C 10 A straight or branched chain alkyl group;

[0035] The reinforcing agent II includes a solidifying material and a solidifying retarder. The solidifying material is a material that can be hydrated and solidified when in contact with water. The compressive strength of the solidifying material is greater than 10 MPa, and the expansion rate is 0.5-1.5%.

[0036] In the present invention, the initiator in Strengthening Agent I enables the polymerizable monomer to controllably undergo secondary crosslinking and solidification under formation conditions, forming a plugging material in the leaking formation. The retarder in Strengthening Agent II enables the consolidation material to controllably solidify under formation conditions, forming a plugging material in the leaking formation.

[0037] In the present invention, the formation conditions refer to the conditions of the formation oil and gas wells. In the present invention, the formation conditions mainly consider temperature, because temperature has the greatest impact on initiators and retarders. The plugging composition of the present invention has a good plugging effect at a temperature of 50-180°C.

[0038] In the present invention, the cross-linkable polymer undergoes a first crosslink upon contact with the cross-linking agent. This crosslinking can occur before or during injection to form a gel. The gel has a mass retention rate of over 90% after 30 minutes of 10 m / min water flow, making the system less susceptible to water washout. Over time, the degree of crosslinking increases, allowing the gel to remain strongly around the wellbore, ultimately forming a plugging material in the leaking formation. The lap shear strength of the plugging material is 0.1-0.14 MPa. The plugging material formed by the plugging composition of the present invention has significant improvements in resistance to water washout and high temperature, and is suitable for use in water-bearing formations below 180°C, particularly those containing flowing water.

[0039] In the present invention, the C1-C 10 Examples of straight-chain or branched alkyl groups include, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, isoheptyl, 2-methylhexyl, 2-ethylhexyl, 1-methylheptyl, 2-methylheptyl, n-octyl, isooctyl, n-nonyl, isononyl and 3,5,5-trimethylhexyl.

[0040] In some preferred embodiments of the present invention, the monomer represented by formula (I) is acrylamide or a derivative thereof.

[0041] In the present invention, the consolidating material in the reinforcing agent II solidifies and has good bonding properties with the water-containing leaking layer. The solidified plugging material will not be dispersed by water after entering the leaking layer. The cross-linkable polymer first cross-links with the cross-linking agent to form a gel, which then solidifies with the consolidating material to form the plugging material.

[0042] In the present invention, when using the plugging composition, the amount and type of the initiator, retarder or curing agent can be controlled to allow the composition to solidify in the leaking formation.

[0043] In some embodiments of the present invention, R1, R2, R 21 、R 22 、R 31 and R 32 Each is independently hydrogen or a C1-C6 linear or branched alkyl group, preferably hydrogen or a C1-C4 linear or branched alkyl group, more preferably hydrogen, methyl or ethyl.

[0044] In some embodiments of the present invention, the metal cross-linking agent is selected from at least one of a zirconium cross-linking agent, a chromium cross-linking agent, and an aluminum cross-linking agent.

[0045] In some embodiments of the present invention, the allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate and ethoxylated pentaerythritol tetraacrylate.

[0046] In the present invention, the crosslinking agent does not contain a water-soluble carbon nanotube crosslinking agent. The present invention has a good crosslinking effect without adding a water-soluble carbon nanotube crosslinking agent.

[0047] In the present invention, when preparing the plugging composition, the crosslinkable polymer can be added in the form of solid particles or in the form of an oil-in-water emulsion. When the crosslinkable polymer is added in the form of solid particles, the plugging composition of the present invention needs to contain a solvent (preferably water) for dissolving the solid matter in the composition; when the crosslinkable polymer is added in the form of an oil-in-water emulsion, the solvent (preferably water) in the plugging composition of the present invention is used to prepare the oil-in-water emulsion.

[0048] The plugging composition of the present invention has low viscosity during the preparation process. After being injected into the well and flowing in the wellbore, the cross-linkable polymer first undergoes cross-linking with the cross-linking agent to form a gel, which encapsulates the other components in the network structure formed by the cross-linking to form a whole. The gel will not be diluted or dispersed when it comes into contact with water. Since the gel contains a large number of hydrogen bonds and has a certain density, it can adhere to the leaking layer and reside around the wellbore of the leaking layer. Under the temperature and pressure conditions of the formation, the initiator in the reinforcing agent I will trigger the monomers shown in formula (I) and dopamine in the system to polymerize and cross-link, further generating a multi-cross-linked plugging material with high compressive strength, thereby plugging the water-containing leaking layer. The dopamine in the plugging composition can enhance the adhesion of the gel to the rock. After the gel is cured, it has good adhesion to the leaking layer, thereby improving the water erosion resistance of the final plugging material.

[0049] In the present invention, the leak-proof composition can undergo primary cross-linking at a certain temperature to form a gel, and then undergo secondary cross-linking to form a solid non-flowable body to achieve complete solidification.

[0050] In some embodiments of the present invention, the cross-linkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the solvent is water; the plugging composition comprises the following components in parts by weight: 0.01-8 parts of a cross-linkable polymer, 0.01-8 parts of a metal cross-linking agent, 0.01-0.9 parts of an allyl cross-linking agent, 3-30 parts of a monomer represented by formula (I), 0.01-3 parts of dopamine, 0.01-8 parts of an initiator, and 100 parts of water.

[0051] In the present invention, the polyacrylamide and / or polyacrylamide derivatives are in the form of solid particles, and water needs to be used as a solvent to first dissolve the solid material and then mix it with the remaining components.

[0052] When the present invention selects each component according to the above-mentioned specific weight parts to prepare the plugging composition, a higher mass retention rate can be obtained during implementation, and the resulting plugging material has stronger compressive strength and better adaptability to high temperature environments.

[0053] In the present invention, the cross-linkable polymer is preferably polyacrylamide, and its weight parts can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and any value in the range composed of any two of the above values.

[0054] In the present invention, the weight portion of dopamine can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, and any value within the range consisting of any two of the above values.

[0055] In the present invention, the weight portion of the metal cross-linking agent can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and any value in the range consisting of any two of the above values.

[0056] In the present invention, the weight proportion of the monomer represented by formula (I) can be 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or any value within the range consisting of any two of the above values.

[0057] In the present invention, the weight portion of the initiator can be 0.01, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, and any value in the range consisting of any two of the above values.

[0058] In the present invention, the allyl crosslinking agent is 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or any value within the range consisting of any two of the above values.

[0059] In some preferred embodiments, the weight proportions of the components in the plugging composition are as follows: 0.01-5 parts of polyacrylamide, 0.01-1 parts of dopamine, 0.01-5 parts of a metal crosslinking agent, 5-25 parts of a monomer represented by formula (I), 0.01-5 parts of an initiator, 0.01-0.5 parts of an allyl crosslinking agent, and 100 parts of water.

[0060] In some embodiments of the present invention, polyacrylamide and dopamine are dissolved in water, and metal crosslinking agent, monomer, allyl crosslinking agent and initiator are added respectively and mixed uniformly to obtain the corresponding plugging slurry of the above plugging composition.

[0061] In some embodiments of the present invention, the weight-average molecular weight of the cross-linkable polymer is 2.5 million to 18 million g / mol, for example, 2.5 million g / mol, 4 million g / mol, 6 million g / mol, 8 million g / mol, 10 million g / mol, 12 million g / mol, 14 million g / mol, 16 million g / mol, 18 million g / mol, and any value within a range consisting of any two of the foregoing values, preferably 3 million to 16 million g / mol. The preferred weight-average molecular weight of the polyacrylamide enables the resulting gel to have higher mass retention and retention capacity under flowing water conditions.

[0062] In the present invention, the weight average molecular weight of the polymer is measured by gel chromatography.

[0063] In some embodiments, the metal crosslinking agent is selected from at least one of a zirconium crosslinking agent, a chromium crosslinking agent, and an aluminum crosslinking agent. During the implementation of the plugging composition of the present invention, polyacrylamide is first crosslinked with the metal crosslinking agent to form a gel.

[0064] In some preferred embodiments, the zirconium cross-linking agent is zirconium trichloride and / or zirconium oxychloride.

[0065] In some preferred embodiments, the chromium cross-linking agent is chromium lactate and / or chromium chloride.

[0066] In some preferred embodiments, the aluminum crosslinking agent is aluminum citrate.

[0067] In some preferred embodiments, the allyl crosslinking agent is at least one selected from N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate and ethoxylated pentaerythritol tetraacrylate.

[0068] In some preferred embodiments, the crosslinking agent further comprises a silicon crosslinking agent. When the plugging composition of the present invention comprises a silicon crosslinking agent, the strength of the system can be improved, and the bonding effect between the gel and the formation can be enhanced.

[0069] In some preferred embodiments, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate and γ-methacryloxypropyltrimethoxysilane (KH570).

[0070] In some preferred embodiments, the weight portion of the silicon crosslinking agent is 0.05-12 parts, for example, 0.05 parts, 0.5 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, and any value in the range consisting of any two of the above values, preferably 0.1-10 parts.

[0071] In some preferred embodiments, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile, and cumene hydroperoxide. These initiators are adaptable to different temperatures and can efficiently initiate crosslinking reactions at different temperatures, allowing the gel to further generate a multi-crosslinked gel with higher compressive strength.

[0072] In some embodiments of the present invention, the enhancer I further comprises at least one of a monomer represented by formula (II), a monomer represented by formula (III), a monomer represented by formula (IV), a monomer represented by formula (V), and a monomer represented by formula (VI); preferably, it comprises a monomer represented by formula (II), a monomer represented by formula (III), a monomer represented by formula (IV), a monomer represented by formula (V), and a monomer represented by formula (VI) at the same time:

[0073] Among them, R3, R4, R6, R7, R 11 、R 12 、R 13 、R 14 、R 15 、R 16 、R 18 、R 19 and R 20 Each independently is hydrogen or C1-C 10 A straight or branched alkyl group; R5 and R 17 Each independently is C1-C 20 straight chain or branched alkylene; R8, R9 and R 10 One of them is C1-C 20 The other two are independently hydrogen or C1-C 10 A straight or branched alkyl group; R' is C1-C 10 is a straight or branched alkylene group; M1 and M2 are each independently H, Na, Li or K; M1 is preferably H or Na; M2 is preferably Na; X1 and X2 are each independently selected from Cl, Br or I, X1 is preferably Cl, and X2 is preferably Cl; m is any integer from 4 to 20, and n is any integer from 3 to 10.

[0074] In some preferred embodiments, R3, R4, R6, R7, R 11 、R 12 、R 13 、R 14 、R 15 、R 16 、R 18 、R 19 and R 20Each is independently hydrogen or a C1-C6 linear or branched alkyl group, preferably hydrogen or a C1-C4 linear or branched alkyl group, more preferably hydrogen, methyl or ethyl.

[0075] In some preferred embodiments, R5 and R 17 Each independently is C1-C 20 The straight or branched chain alkylene group includes, but is not limited to, methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene and hexylene; R5 is preferably isobutylene; R 17 Preferred is ethylene.

[0076] In some preferred embodiments, R' is C1-C 10 The straight or branched chain alkylene group includes, but is not limited to, methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene and hexylene; R' is preferably a methylene group.

[0077] In some preferred embodiments, R8, R9 and R 10 One of them is C8-C 20 A straight or branched chain alkyl group, preferably C 18 The remaining two are methyl groups.

[0078] In some embodiments, the monomer represented by formula (II) is 2-acrylamide-2-methylpropanesulfonic acid and / or sodium 2-acrylamide-2-methylpropanesulfonate, the monomer represented by formula (III) is octadecyldimethylallylammonium chloride, the monomer represented by formula (IV) is allyl nonylphenol polyoxyethylene ether, the monomer represented by formula (V) is sodium acrylate, and the monomer represented by formula (VI) is acryloyloxyethyltrimethylammonium chloride.

[0079] In some preferred embodiments, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (II) is 0.2-25 parts, preferably 2-20 parts.

[0080] In some preferred embodiments, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (III) is 0.5-20 parts, preferably 1-15 parts.

[0081] In some preferred embodiments, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (IV) is 0.2-5 parts, preferably 0.5-4 parts.

[0082] In some preferred embodiments, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (V) is 0.5-20 parts, preferably 1-15 parts.

[0083] In some preferred embodiments, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (VI) is 0.5-10 parts, preferably 1-8 parts.

[0084] In some preferred embodiments, the plugging composition further comprises a weighting agent; preferably, the weighting agent is selected from at least one of calcium carbonate, barite and iron ore powder, preferably barite.

[0085] In some preferred embodiments, based on 100 parts by weight of water, the weight of the weighting agent is 5-200 parts, preferably 10-150 parts.

[0086] In some embodiments, the plugging composition further comprises a retarder.

[0087] In some preferred embodiments, the retarder is p-benzoquinone.

[0088] In some preferred embodiments, based on 100 parts by weight of water, the weight of the retarder is no more than 1 part, preferably 0.1-0.6 parts.

[0089] The density of the plugging composition at 25°C is 1-2 g / cm 3 , preferably 1.2-1.65g / cm 3 .

[0090] In other embodiments of the present invention, the cross-linkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the cross-linkable polymer exists in the form of an oil-in-water emulsion, and the oil-in-water emulsion includes the cross-linkable polymer, oil, water and an emulsifier; the weight parts of each component in the plugging composition are as follows: 100 parts of oil-in-water emulsion, 0.01-8 parts of cross-linking agent, 3-30 parts of monomer represented by formula (I), 0.01-2 parts of dopamine and 0.01-8 parts of initiator.

[0091] In some preferred embodiments of the present invention, the mass ratio of the cross-linkable polymer, oil, water, and emulsifier is 0.5-15:100:50-100:0.05-10, for example, 0.5:100:50:0.05, 3:100:60:3, 10:100:80:7, 13:100:90:2, 8:100:92:5, 15:100:100:10, and any value in a range consisting of any two of the foregoing values, more preferably 1-10:100:60-90:0.1-5. Such a mass ratio can result in a strong gel having a higher mass retention rate.

[0092] In the present invention, the water-in-oil emulsion is prepared by a method comprising the following steps:

[0093] First, polyacrylamide and / or polyacrylamide derivatives are added to water and stirred, an emulsifier is introduced into the oil phase and stirred to dissolve, and then the polyacrylamide solution and / or polyacrylamide derivative solution is slowly added to the oil phase, and stirred and emulsified at a stirring speed of 8000-12000 r / min to obtain a water-in-oil emulsion.

[0094] When polyacrylamide and polyacrylamide derivatives are in the form of oil-in-water emulsion, after the plugging composition enters the leaking layer and encounters formation water, the oil-in-water emulsion will break, and the polyacrylamide and polyacrylamide derivatives will be immediately released to cross-link with the cross-linking agent in the system to form a gel, and the monomers and initiators will be encapsulated in the network structure formed by the cross-linking, so that the system will not be dispersed by water.

[0095] In some preferred embodiments, the oil is selected from at least one of waste white oil, waste diesel, waste engine oil, and waste edible oil. The oil in the water-in-oil emulsion of the present invention can use waste oil phase, turning waste into treasure.

[0096] In some preferred embodiments, the polyacrylamide is anionic polyacrylamide, and the weight average molecular weight of the anionic polyacrylamide is 2.5-10 million g / mol, for example, 2.5 million g / mol, 4 million g / mol, 6 million g / mol, 8 million g / mol, 10 million g / mol, and any value in the range consisting of any two of the above values, preferably 3-8 million g / mol.

[0097] In the present invention, the weight average molecular weight of the polymer is measured by gel chromatography.

[0098] In some preferred embodiments, the emulsifier is selected from at least one of octylphenol polyoxyethylene ether-10 (OP-10), octylphenol polyoxyethylene ether-15 (OP-15), nonylphenol polyoxyethylene ether-10 (NP-10), nonylphenol polyoxyethylene ether-15 (NP-15), Tween-20 (T-20), Tween-60 (T-60), Span-80 (S-80), Span-85 (S-85) and sodium dodecylbenzene sulfonate.

[0099] In some embodiments of the present invention, the enhancer I further comprises at least one of a monomer represented by formula (II), a monomer represented by formula (III), a monomer represented by formula (IV), a monomer represented by formula (V), and a monomer represented by formula (VI); preferably, it comprises a monomer represented by formula (II), a monomer represented by formula (III), a monomer represented by formula (IV), a monomer represented by formula (V), and a monomer represented by formula (VI) at the same time:

[0100] Among them, R3, R4, R6, R7, R 11 、R12 、R 13 、R 14 、R 15 、R 16 、R 18 、R 19 and R 20 Each independently is hydrogen or C1-C 10 A straight or branched alkyl group; R5 and R 17 Each independently is C1-C 20 straight chain or branched alkylene; R8, R9 and R 10 One of them is C1-C 20 The other two are independently hydrogen or C1-C 10 A straight or branched alkyl group; R' is C1-C 10 is a straight or branched alkylene group; M1 and M2 are each independently H, Na, Li or K; M1 is preferably H or Na; M2 is preferably Na; X1 and X2 are each independently selected from Cl, Br or I, X1 is preferably Cl, and X2 is preferably Cl; m is any integer from 4 to 20, and n is any integer from 3 to 10.

[0101] The specific preferred embodiments of each substituent can be found in the previous description and will not be repeated here.

[0102] In some embodiments, the monomer represented by formula (II) is 2-acrylamide-2-methylpropanesulfonic acid and / or sodium 2-acrylamide-2-methylpropanesulfonate, the monomer represented by formula (III) is octadecyldimethylallylammonium chloride, the monomer represented by formula (IV) is allyl nonylphenol polyoxyethylene ether, the monomer represented by formula (V) is sodium acrylate, and the monomer represented by formula (VI) is acryloyloxyethyltrimethylammonium chloride.

[0103] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (II) is 0.2-20 parts, preferably 2-15 parts.

[0104] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (III) is 0.5-20 parts, preferably 1-15 parts.

[0105] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (IV) is 0.2-5 parts, preferably 0.5-4 parts.

[0106] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (V) is 0.5-20 parts, preferably 1-15 parts.

[0107] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (VI) is 0.5-10 parts, preferably 1-8 parts.

[0108] In the present invention, the water-in-oil emulsion, monomer, initiator and cross-linking agent are mixed and stirred evenly to obtain the corresponding plugging slurry of the plugging composition.

[0109] When the present invention selects each component according to the above-mentioned specific weight parts to prepare the plugging composition, a higher mass retention rate can be obtained during implementation, and the resulting plugging material has stronger compressive strength and better adaptability to high temperature environments.

[0110] The weight proportion of the monomer represented by formula (I) can be 3 parts, 5 parts, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, or any value within the range consisting of any two of the above values.

[0111] The weight portion of the initiator can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and any value in the range consisting of any two of the above values.

[0112] The weight portion of the cross-linking agent can be 0.01 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, and any value in the range consisting of any two of the above values.

[0113] In some preferred embodiments, the weight proportions of the components in the plugging composition are as follows: 100 parts of water-in-oil emulsion, 5-25 parts of the monomer represented by formula (I), 0.01-1 part of dopamine, 0.01-5 parts of initiator and 0.01-5 parts of cross-linking agent.

[0114] In some preferred embodiments of the present invention, the initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile, and cumene hydroperoxide. These preferred initiators are adaptable to different temperatures and can efficiently initiate crosslinking reactions at different temperatures, thereby further forming a multi-crosslinked gel with high compressive strength.

[0115] In some preferred embodiments, the cross-linking agent comprises an allyl cross-linking agent and / or an organometallic cross-linking agent.

[0116] In some preferred embodiments, the cross-linking agent comprises a mixture of an allyl cross-linking agent and an organometallic cross-linking agent, wherein the mass ratio of the allyl cross-linking agent to the organometallic cross-linking agent is 1:0.3-8, preferably 1:0.5-5.

[0117] In some preferred embodiments, the allyl crosslinking agent is at least one selected from N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate and ethoxylated pentaerythritol tetraacrylate.

[0118] In some preferred embodiments, the organometallic crosslinking agent is selected from at least one of an organozirconium crosslinking agent, an organochromium crosslinking agent, and an organoaluminum crosslinking agent.

[0119] In some preferred embodiments, the organic zirconium cross-linking agent is zirconium citrate.

[0120] In some preferred embodiments, the organic chromium cross-linking agent is chromium lactate.

[0121] In some preferred embodiments, the organoaluminum crosslinking agent is aluminum citrate.

[0122] In some preferred embodiments, the cross-linking agent further comprises a silicon cross-linking agent.

[0123] When the cross-linking agent of the present invention includes a silicon cross-linking agent, the strength of the system can be improved, and the bonding effect between the gel and the formation can be increased.

[0124] In some preferred embodiments, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate and γ-methacryloxypropyltrimethoxysilane (KH570).

[0125] In some preferred embodiments, the crosslinking agent is a mixture of an allyl crosslinking agent, an organometallic crosslinking agent and a silicon crosslinking agent, wherein the mass ratio of the allyl crosslinking agent, the organometallic crosslinking agent and the silicon crosslinking agent is 1:0.3-8:0.1-12, preferably 1:0.5-5:0.2-10.

[0126] In some preferred embodiments, the plugging composition further comprises a weighting agent.

[0127] In some preferred embodiments, the weighting agent is selected from at least one of calcium carbonate, barite and iron ore powder, preferably barite.

[0128] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight of the weighting agent is 5-120 parts, preferably 10-100 parts.

[0129] In some embodiments, the plugging composition further comprises a retarder.

[0130] In some preferred embodiments, the retarder is p-benzoquinone.

[0131] In some preferred embodiments, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the retarder is no more than 1 part, preferably 0.1-0.6 parts.

[0132] In some preferred embodiments, the density of the plugging composition at 25°C is 1.2-1.78 g / cm 3 .

[0133] In some other embodiments of the present invention, the plugging composition further includes a salt-resistant polymer, which together with the cross-linkable polymer constitutes a water-indispersible material; the weight proportions of the components in the plugging composition are as follows: 10-15 parts of water-indispersible material, 0.1-4 parts of a cross-linking agent, 50-200 parts of a consolidating material, and 100 parts of water.

[0134] In the present invention, the plugging composition preferably comprises, by weight, 12-15 parts of a water-indispersible material, 1-3 parts of a crosslinking agent, 150-200 parts of a consolidating material, 0.5-5 parts of a setting retarder, and 100 parts of water. These optimal conditions improve the performance of the consolidated plugging slurry, namely, achieving high mass retention, high adhesion, and high compressive strength.

[0135] When the present invention selects each component according to the above-mentioned specific weight parts to prepare the plugging composition, a higher mass retention rate can be obtained during implementation, and the resulting plugging material has stronger compressive strength and better adaptability to high temperature environments.

[0136] In some preferred embodiments, the cross-linkable polymer is a non-ionic polymer, preferably selected from polyacrylamide and / or polyacrylamide derivatives.

[0137] In some preferred embodiments, the weight-average molecular weight of the cross-linkable polymer is 2 million to 14 million g / mol, for example, 2 million g / mol, 2.5 million g / mol, 3 million g / mol, 4 million g / mol, 5 million g / mol, 6 million g / mol, 7 million g / mol, 8 million g / mol, 9 million g / mol, 10 million g / mol, 12 million g / mol, 14 million g / mol, or any value within a range consisting of any two of the foregoing values, preferably 5 million to 14 million g / mol. The preferred weight-average molecular weight of the polyacrylamide and polyacrylamide derivatives enables the resulting gel to have a higher mass retention rate and retention capacity under flowing water conditions.

[0138] In the present invention, the weight average molecular weight of the polymer is measured by gel chromatography.

[0139] In some preferred embodiments, the salt-resistant polymer is selected from at least one of SMPFL-C, SMHV-C and SMVIS-1.

[0140] In the present invention, SMPFL-C, SMHV-C and SMVIS-1 were purchased from Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0141] In the present invention, the water-insoluble material comprises a salt-resistant polymer and a nonionic polymer; the mass ratio of the salt-resistant polymer to the nonionic polymer is 10:(0.5-3), preferably 10:(1-2). The salt-resistant polymer and the nonionic polymer are beneficial for improving the mass retention rate of the consolidation plugging slurry, allowing it to reside in the leaking layer under flowing water and not be dispersed by water.

[0142] In the present invention, the preparation method of the water-indispersible material has a wide range of options, as long as the weight ratio of each component in the water-indispersible material meets the above definition.

[0143] In some preferred embodiments, the consolidating material includes cement or lime, slag, bentonite, gypsum and an acidic substance; the acidic substance is hydrochloric acid and / or hydroxyethylidene diphosphonic acid.

[0144] In some preferred embodiments, the mass ratio of the cement or lime, slag, bentonite, gypsum and acidic substance is 4-10:8-20:1-2:1-3:0.2-1.

[0145] In the present invention, under the action of the cross-linking agent, after the solidifying material is solidified, the bonding performance with the water-containing leaking layer is better.

[0146] In some preferred embodiments, the solid retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid polymer and / or hydroxycarboxylic acid polymer.

[0147] Furthermore, the weight average molecular weight of the 2-acrylamide-2-methylpropanesulfonic acid polymer is 1 to 5 million g / mol.

[0148] Furthermore, the hydroxycarboxylic acid polymer may be SCR-3, wherein SCR-3 is a hydroxycarboxylic acid polymer produced by Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0149] In the present invention, based on 100 parts by weight of water, the weight of the retarder is no more than 5 parts, preferably 0.1-2 parts.

[0150] In some preferred embodiments, based on 100 parts by weight of water, the plugging composition further comprises 0-40 parts by weight of a density regulator.

[0151] In some preferred embodiments, the density modifier can be a weighting agent or a lightening agent; the weighting agent is at least one of calcium carbonate, barite, or iron ore powder; and the lightening agent is at least one of buoyant beads, hollow glass microspheres, and polymer hollow microspheres. All of these components are commercially available. The present invention allows the density of the plugging composition to be adjusted by adjusting the amount of density modifier added.

[0152] In some embodiments of the present invention, the density of the plugging composition after mixing at 25°C is 1-2 g / cm 3 , preferably 1.2-1.65g / cm 3 .

[0153] In the present invention, unless otherwise specified, the density is measured using the method of GB / T16783.1-2014.

[0154] A second aspect of the present invention provides a plugging material, which is obtained by curing the aforementioned plugging composition.

[0155] In some embodiments of the present invention, the curing temperature is 50-180°C.

[0156] In some embodiments of the present invention, the compressive strength of the plugging material is 15-25 MPa.

[0157] The third aspect of the present invention provides the use of the aforementioned plugging composition or the aforementioned plugging material in plugging oil well formations; preferably, the oil well formation is an oil well formation containing flowing water at a temperature of 50-180°C.

[0158] The plugging material formed by the plugging composition of the present invention has the properties of resistance to water dilution and high temperature. After entering the water-bearing formation, especially the formation containing flowing water, it can stay in the leaking layer and eventually solidify under the formation conditions to form a plug with a compressive strength of 15-25MPa, thereby solving the leakage problem of the formation containing flowing water.

[0159] After the plugging composition of the present invention is injected into a water-containing formation, polyacrylamide and / or polyacrylamide derivatives react with a cross-linking agent to generate a gel, and other components are coated in the network structure formed by the cross-linking, so that the system will not be dispersed by water. After residence in the formation under the temperature and pressure environment, the initiator initiates polymerization and cross-linking or the solidified material solidifies, further generating a multi-cross-linked plugging material with high compressive strength, thereby plugging the water-containing leaking layer.

[0160] The plugging composition of the present invention is applicable to any water-bearing stratum and has an effect significantly better than that of the existing plugging composition for flowing water-bearing strata in a wide temperature range.

[0161] When the plugging composition or plugging material of the present invention is used to plug formation cracks, especially formation cracks containing flowing water, it can have high compressive strength in formation environments with different temperatures, thereby solving the leakage problem of water-containing formations.

[0162] A fourth aspect of the present invention provides an oil well plugging method, which includes directly injecting the aforementioned plugging composition into the cracks in the oil well formation so that the plugging composition forms a gel during the injection process into the formation, or injecting the aforementioned plugging composition into the cracks in the oil well formation after forming a gel, and under formation conditions, the gel solidifies at the leaking formation to form a plugging material; wherein, the mass retention rate of the gel after being flushed at a water flow rate of 10m / min for 30min at 50-180°C is above 90%; and the lap shear strength of the plugging material is 0.1-0.14MPa.

[0163] During the injection process, the polyacrylamide and / or polyacrylamide derivatives undergo a crosslinking reaction with a crosslinking agent to form a gel. This crosslinked network encapsulates the other components, preventing the system from being dispersed by water and achieving a mass retention rate of up to 96% against water erosion. The gel formed in the present invention can be strongly retained around the wellbore and solidifies under the temperature and pressure of the formation to form a plugging material with a strength of up to 25 MPa, ultimately plugging the leaking layer.

[0164] Compared with existing plugging compositions, the plugging material formed by the plugging composition of the present invention has significant improvements in water dilution resistance and high temperature resistance. The plugging material of the present invention can be applied to water-bearing formations with a temperature of 50-180°C, especially formations containing flowing water.

[0165] In the present invention, an appropriate plugging composition is selected based on the on-site formation conditions. Given that temperature has the greatest impact on the reaction, the simulated formation conditions primarily consider formation temperature. Considering that the underground is a confined space, gelation and solidification in the formation can be simulated under confined conditions at a certain temperature or by injection into water at a certain temperature. If the resulting plugging slurry, after mixing the plugging mixture, gels and solidifies under confined conditions at a certain temperature, it is assumed that it will also gel and solidify under similar formation conditions. Simultaneously, water injection is used to simulate formations containing flowing water.

[0166] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or those recommended by the manufacturer. All reagents and instruments used, if no manufacturer is specified, are commercially available conventional products.

[0167] Chemical consolidation material SMHD-1, a commercial product of Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0168] The chemical consolidation material SMHD-2 is a commercial product of Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0169] SMPFL-C is a commercial product of Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0170] SMHV-C is a commercial product of Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0171] SMVIS-1 is a commercial product of Sinopec Petroleum Engineering Technology Research Institute Co., Ltd.

[0172] Test method:

[0173] Density: Tested using a density meter using the method in GBT 16783.1-2014.

[0174] Compressive strength: tested using the method in GB / T 50266-99.

[0175] Overlap shear strength: The test was conducted using the GB 7124-1986 adhesive tensile shear strength determination method. The difference was that the metal was replaced with core pieces of the same specifications. The gel was applied to the overlapping area of ​​the limestone core pieces, and two core pieces prepared in this way were lightly covered. The samples were then pressed under a pressure of 0.5 MPa for 1 hour, and the overlap shear strength of the cured samples was measured.

[0176] Compressive strength: The formed gel was allowed to stand for 30 minutes. 500 mL of the gel was taken and injected into a testing apparatus (for details, see CN113123756A, a simulation apparatus for plugging water-bearing leakage zones) under water flow. The water flow rate was set to 10 m / min and the gel injection rate to 20 m / min. After the gel was injected, water was continued to be injected. After the formed gel was completely cured, water was continued to be injected. The maximum pressure on the pressure gauge 17 (as shown in FIG. 1 of CN113123756A) was read. This was the compressive strength of the cured sample.

[0177] Mass retention rate: The formed gel was allowed to stand for 30 minutes. 500 mL of the gel was then injected into a testing apparatus (see CN113123756A for details, which describes a simulation apparatus for plugging leaks in water-bearing loss zones) under water flow. The water flow rate was set at 10 m / min and the gel injection rate at 20 m / min. After the gel was injected, water was continued to be injected for 30 minutes. The sample was then removed and its mass retention rate was calculated.

[0178] Mass retention rate = mass of sample after flushing / mass of injected gel*100%.

[0179] Example 1

[0180] A plugging slurry was prepared according to the formula of the plugging composition in Example 1 in Table 1. The specific preparation method was as follows: 100 parts of water were weighed, 0.01 parts of polyacrylamide were added, and the mixture was stirred at 1000 r / min until completely dissolved. Then, 0.01 parts of zirconium oxychloride were added and stirred for 5 minutes, and 1 part of dopamine was added and stirred for 5 minutes. Then, 0.005 parts of ethoxylated trimethylolpropane triacrylate, 0.005 parts of pentaerythritol tetraacrylate, 10 parts of acrylamide, 2 parts of 2-acrylamide-2-methylpropanesulfonic acid, 3 parts of octadecyldimethylallylammonium chloride, 0.5 parts of allyl nonylphenol polyoxyethylene ether, 0.1 parts of ethyl silicate, 0.01 parts of azobisisobutyronitrile and 10 parts of iron ore powder were added to the above solution in sequence, and the mixture was stirred and mixed evenly to obtain a plugging slurry.

[0181] According to the above method, the density of the plugging slurry at 25°C is 1.3g / cm 3 Under sealed conditions at 100°C, the plugging slurry took 15 minutes to gel and 30 minutes to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 95%. After the gel completely solidified to form a plugging material, its compressive strength was tested to reach 7MPa, its lap shear strength was 0.11MPa, and its compressive strength was 22.3MPa.

[0182] Example 2

[0183] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 2 in Table 1.

[0184] According to the above method, the density of the plugging slurry at 25°C is 1.5g / cm 3 Under closed conditions at 80°C, the plugging slurry took 22 minutes to form a gel and 60 minutes to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93%. After the gel completely solidified to form a plugging material, its compressive strength was tested to reach 7MPa, its lap shear strength was 0.10MPa, and its compressive strength was 24.1MPa.

[0185] Example 3

[0186] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 3 in Table 1.

[0187] According to the above method, the density of the plugging slurry at 25°C is 1.2g / cm3 Under sealed conditions at 50°C, the plugging slurry took 15 minutes to gel and 80 minutes to fully solidify. Using a testing device, the resulting gel was flushed with water, and its mass retention was calculated to be 96%. After the gel fully solidified to form the plugging material, testing revealed a compressive strength of 7MPa, a lap shear strength of 0.13MPa, and a compressive strength of 25MPa.

[0188] Example 4

[0189] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 4 in Table 1.

[0190] According to the above method, the density of the plugging slurry at 25°C is 1.38g / cm 3 Under closed conditions at 120°C, the plugging slurry took 23 minutes to form a gel and 67 minutes to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 94.7%. After the gel was fully solidified to form a plugging material, its compressive strength was tested to reach 7MPa, its lap shear strength was 0.12MPa, and its compressive strength was 21.9MPa.

[0191] Example 5

[0192] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 5 in Table 1.

[0193] According to the above method, the density of the plugging slurry at 25°C is 1.65g / cm 3 Under closed conditions at 150°C, the plugging slurry took 10 minutes to form a gel and 30 minutes to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93.7%. After the gel was fully solidified to form a plugging material, its compressive strength was tested to reach 7MPa, its lap shear strength was 0.14MPa, and its compressive strength was 22.8MPa.

[0194] Example 6

[0195] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 3 in Table 1, except that no silicon cross-linking agent was added.

[0196] According to the above method, the density of the plugging slurry at 25°C is 1.2g / cm 3Under closed conditions at 50°C, the plugging slurry took 15 minutes to gel and 80 minutes to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 90%. After the gel completely solidified to form a plugging material, its compressive strength was tested to reach 7MPa, its lap shear strength was 0.11MPa, and its compressive strength was 18MPa.

[0197] Comparative Example 1

[0198] According to the method of Example 1, a plugging slurry was prepared according to the formula of the plugging composition in Example 3 in Table 1, except that dopamine was not added.

[0199] According to the above method, the density of the plugging slurry at 25°C is 1.2g / cm 3 . Under closed conditions at 50°C, the plugging slurry takes 20 minutes to form a gel and 90 minutes to fully solidify. Using a testing device, the formed gel was injected with water and flushed, and its mass retention rate was calculated to be only 65%. After the gel was completely solidified to form a plugging material, its bearing strength was tested to be only 1.2MPa, the lap shear strength was only 0.016MPa, and the compressive strength was 12MPa. It can be seen that the final plugging material has a poor retention effect in the flowing water leakage layer.

[0200] Table 1

[0201] Example 7

[0202] The plugging slurry was prepared according to the formula of the plugging composition in Example 7 in Table 2.

[0203] (1) Preparation of water-in-oil emulsion:

[0204] First, 5 parts of anionic polyacrylamide with a weight-average molecular weight of 3,000,000 g / mol were added to 90 parts of water and stirred to dissolve to obtain a polyacrylamide solution; 3 parts of emulsifier OP-10 were introduced into 100 g of waste white oil and stirred to dissolve to obtain an oil phase; then, the obtained polyacrylamide solution was slowly added to the obtained oil phase, and stirred and emulsified at a stirring speed of 8,000 r / min to obtain a water-in-oil emulsion;

[0205] (2) Preparation of plugging slurry:

[0206] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0207] According to the above method, the density of the plugging slurry at 25°C is 1.05g / cm 3The resulting plugging slurry was injected into 60°C water. It took 45 seconds for the plugging slurry to form a gel and 40 minutes for it to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 97.5%. After the gel was completely solidified to form a plugging material, its compressive strength was tested to be 7MPa, its lap shear strength was 0.13MPa, and its compressive strength was 18.8MPa.

[0208] Example 8

[0209] The plugging slurry was prepared according to the formula of the plugging composition in Example 8 in Table 2.

[0210] (1) Preparation of water-in-oil emulsion:

[0211] First, 4 parts of anionic polyacrylamide with a weight-average molecular weight of 4,000,000 g / mol were added to 80 parts of water and stirred to dissolve to obtain a polyacrylamide solution; 1 part of emulsifier NP-15 was introduced into 100 g of waste diesel and stirred to dissolve to obtain an oil phase; then the obtained polyacrylamide solution was slowly added to the obtained oil phase, and stirred and emulsified at a stirring speed of 9,000 r / min to obtain a water-in-oil emulsion;

[0212] (2) Preparation of plugging slurry:

[0213] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0214] According to the above method, the density of the plugging slurry at 25°C is 1.05g / cm 3 The resulting plugging slurry was injected into 90°C water. It took 20 seconds for the plugging slurry to form a gel and 75 minutes for it to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 95.5%. After the gel was completely solidified to form a plugging material, its compressive strength was tested to be 7MPa, its lap shear strength was 0.12MPa, and its compressive strength was 19.8MPa.

[0215] Example 9

[0216] The plugging slurry was prepared according to the formula of the plugging composition in Example 9 in Table 2.

[0217] (1) Preparation of water-in-oil emulsion:

[0218] First, 2 parts of anionic polyacrylamide with a weight-average molecular weight of 8,000,000 g / mol were added to 60 parts of water and stirred to dissolve to obtain a polyacrylamide solution; 4 parts of emulsifier OP-15 were introduced into 100 g of waste edible oil and stirred to dissolve to obtain an oil phase; then, the obtained polyacrylamide solution was slowly added to the obtained oil phase, and stirred and emulsified at a stirring speed of 12,000 r / min to obtain a water-in-oil emulsion;

[0219] (2) Preparation of plugging slurry:

[0220] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0221] According to the above method, the density of the plugging slurry at 25°C is 1.36 g / cm 3 The resulting plugging slurry was injected into 140°C water. It took 10 seconds for the plugging slurry to form a gel and 39 minutes for it to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93.1%. After the gel was completely solidified to form a plugging material, its compressive strength was tested to be 7MPa, its lap shear strength was 0.12MPa, and its compressive strength was 16.8MPa.

[0222] Example 10

[0223] The plugging slurry was prepared according to the formula of the plugging composition in Example 10 in Table 2.

[0224] (1) Preparation of water-in-oil emulsion:

[0225] First, 1 part of anionic polyacrylamide with a weight-average molecular weight of 4.5 million g / mol was added to 80 parts of water and stirred to dissolve to obtain a polyacrylamide solution; 0.1 part of emulsifier S-80 was introduced into 100 g of waste engine oil and stirred to dissolve to obtain an oil phase; then, the obtained polyacrylamide solution was slowly added to the obtained oil phase, and stirred and emulsified at a stirring speed of 10,000 r / min to obtain a water-in-oil emulsion;

[0226] (2) Preparation of plugging slurry:

[0227] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0228] According to the above method, the density of the plugging slurry at 25°C is 1.23g / cm 3The resulting plugging slurry was injected into 100°C water. It took 40 seconds for the plugging slurry to form a gel and 35 minutes for it to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 97.8%. After the gel was completely solidified to form a plugging material, its compressive strength was tested to be 7MPa, its lap shear strength was 0.11MPa, and its compressive strength was 17.5MPa.

[0229] Example 11

[0230] The plugging slurry was prepared according to the formula of the plugging composition in Example 11 in Table 2.

[0231] (1) Preparation of water-in-oil emulsion:

[0232] First, 10 parts of anionic polyacrylamide with a weight-average molecular weight of 6,000,000 g / mol were added to 70 parts of water and stirred to dissolve to obtain a polyacrylamide solution; 5 parts of emulsifier T-20 were introduced into 100 g of waste edible oil and stirred to dissolve to obtain an oil phase; then, the obtained polyacrylamide solution was slowly added to the obtained oil phase, and stirred and emulsified at a stirring speed of 9,000 r / min to obtain a water-in-oil emulsion;

[0233] (2) Preparation of plugging slurry:

[0234] The water-in-oil emulsion obtained in step (1) is mixed evenly with other components to obtain a plugging slurry.

[0235] According to the above method, the density of the plugging slurry at 25°C is 1.78g / cm 3 The resulting plugging slurry was injected into 110°C water, generating a gel in 25 seconds and fully solidifying in 38 minutes. Using a testing device, the resulting gel was flushed with water, and its mass retention rate was calculated to be 97%. After the gel completely solidified to form a plugging material, its compressive strength was tested to be 7MPa, its lap shear strength was 0.14MPa, and its compressive strength was 17MPa.

[0236] Example 12

[0237] The plugging slurry was prepared according to the method of Example 7. The plugging slurry was prepared according to the formula of the plugging composition in Example 7 in Table 2, except that no silicon cross-linking agent was added.

[0238] According to the above method, the density of the plugging slurry at 25°C is 1.05g / cm 3The resulting plugging slurry was injected into 60°C water. It took 45 seconds for the plugging slurry to form a gel and 40 minutes for it to fully solidify. Using a testing device, the formed gel was flushed with water, and its mass retention rate was calculated to be 93%. After the gel was completely solidified to form a plugging material, its compressive strength was tested to be 6.5MPa, its lap shear strength was 0.1MPa, and its compressive strength was 15.6MPa.

[0239] Comparative Example 2

[0240] A plugging slurry was prepared according to the method of Example 7, except that no polyacrylamide was added to the water-in-oil emulsion.

[0241] After testing, it was found that the plugging slurry of this comparative example could not generate gel.

[0242] Table 2

[0243] Example 13

[0244] Step 1: Preparation of a water-insoluble material: 20 g of a salt-resistant polymer SMPFL-C and 2 g of polyacrylamide with a weight-average molecular weight of 5,000,000 g / mol were mixed to obtain a water-insoluble material.

[0245] Step 2: Preparation of a cross-linking agent: 100 g of water glass, 100 g of zirconium citrate, and 5 g of polyethyleneimine were mixed, and then 90 g of water and 0.2 g of sodium dodecylbenzenesulfonate were added, and stirred at 65° C. to obtain a cross-linking agent;

[0246] Step 3: Mix 100 g of water, 150 g of chemical consolidation material SMHD-1, 12 g of the water-indispersible material obtained in step 1, 1 g of the cross-linking agent obtained in step 2 and 1 g of 2-acrylamide-2-methylpropanesulfonic acid polymer to obtain a plugging slurry.

[0247] According to the above method, the density of the plugging slurry at 25°C is 1.65g / cm 3 Under sealed conditions at 90°C, the plugging slurry took 30 minutes to gel and 5.5 hours to fully solidify. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 95.2%. After the gel fully solidified to form a plugging material, testing showed a compressive strength of 7 MPa, a lap shear strength of 0.14 MPa, and a compressive strength of 21.4 MPa.

[0248] Example 14

[0249] Step 1: Preparation of a water-insoluble material: 10 g of a salt-resistant polymer SMVIS-1 and 2 g of polyacrylamide having a weight-average molecular weight of 10 million g / mol were mixed to obtain a water-insoluble material.

[0250] Step 2: Preparation of a crosslinking agent: 100 g of ethyl orthosilicate, 80 g of zirconium citrate, and 7 g of polyethyleneimine were mixed, and then 60 g of water and 0.5 g of sodium dodecylbenzenesulfonate were added, and stirred at 40° C. to obtain a crosslinking agent;

[0251] Step 3: Mix 100 g of water, 200 g of chemical consolidation material SMHD-1, 12 g of the water-indispersible material obtained in step 1, 3 g of the cross-linking agent obtained in step 2, 4 g of hydroxycarboxylic acid polymer and 20 g of floating beads to obtain a plugging slurry.

[0252] According to the above method, the density of the plugging slurry at 25°C is 1.72g / cm 3 Under sealed conditions at 120°C, the plugging slurry gelled in 20 minutes and fully solidified in 4.5 hours. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 94.8%. After the gel fully solidified to form a plugging material, testing revealed a compressive strength of 7 MPa, a lap shear strength of 0.13 MPa, and a compressive strength of 23.8 MPa.

[0253] Example 15

[0254] Step 1: Preparation of a water-insoluble material: 20 g of a salt-resistant polymer SMHV-C and 4 g of a nonionic polyacrylamide having a weight-average molecular weight of 14 million g / mol were mixed to obtain a water-insoluble material.

[0255] Step 2: Preparation of a crosslinking agent: 100 g of KH560, 150 g of chromium lactate, and 3 g of polyethyleneimine were mixed, and then 50 g of water and 1 g of sodium dodecylbenzenesulfonate were added, and stirred at 50° C. to obtain a crosslinking agent;

[0256] Step 3: Mix 100 g of water, 180 g of chemical consolidation material SMHD-2, 15 g of the water-indispersible material obtained in step 1, 2.5 g of the cross-linking agent obtained in step 2, 3.5 g of hydroxycarboxylic acid polymer and 30 g of barite to obtain a plugging slurry.

[0257] According to the above method, the density of the plugging slurry at 25°C is 1.69g / cm 3Under sealed conditions at 150°C, the plugging slurry took 20 minutes to gel and 3.2 hours to fully solidify. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 93.7%. After the gel fully solidified into a plugging material, testing revealed a compressive strength of 7 MPa, a lap shear strength of 0.12 MPa, and a compressive strength of 22.7 MPa.

[0258] Example 16

[0259] A plugging slurry was prepared according to the method of Example 13, except that in step 3, 100 g of water, 50 g of the chemical consolidation material SMHD-1, 10 g of the water-indispersible material and 0.1 g of the cross-linking agent were stirred uniformly to obtain the plugging slurry.

[0260] According to the above method, the density of the plugging slurry at 25°C is 1.5g / cm 3 Under sealed conditions at 80°C, the plugging slurry took 40 minutes to gel and 6 hours to fully solidify. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 91.3%. After the gel fully solidified into a plugging material, testing revealed a compressive strength of 7 MPa, a lap shear strength of 0.10 MPa, and a compressive strength of 17.5 MPa.

[0261] Example 17

[0262] A consolidation plugging slurry was prepared according to the method of Example 13, except that, in step 1, 20 g of SMPFL-C was uniformly mixed with 6 g of polyacrylamide having a weight-average molecular weight of 5,000,000 g / mol to obtain a water-indispersible material; and in step 2, 100 g of water glass was mixed with 10 g of zirconium citrate and 10 g of polyethyleneimine, and then 90 g of water and 0.2 g of sodium dodecylbenzenesulfonate were added, and the mixture was stirred uniformly at 65° C. to obtain a cross-linking agent.

[0263] According to the above method, the density of the plugging slurry at 25°C is 1.65g / cm 3 Under sealed conditions at 100°C, the plugging slurry gelled in 25 minutes and fully solidified in 5 hours. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 94.1%. After the gel fully solidified to form a plugging material, testing showed a compressive strength of 7 MPa, a lap shear strength of 0.11 MPa, and a compressive strength of 20.4 MPa.

[0264] Example 18

[0265] A consolidation plugging slurry was prepared according to the method of Example 13, except that 100 g of water glass was not added in step 2, that is, step 2: preparation of a cross-linking agent: 100 g of zirconium citrate and 5 g of polyethyleneimine were mixed, and then 90 g of water and 0.2 g of sodium dodecylbenzenesulfonate were added, and stirred at 65°C to obtain a cross-linking agent.

[0266] According to the above method, the density of the plugging slurry at 25°C is 1.65g / cm 3 Under sealed conditions at 90°C, the plugging slurry took 30 minutes to gel and 5.3 hours to fully solidify. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 92.3%. After the gel fully solidified into a plugging material, testing showed a compressive strength of 7 MPa, a lap shear strength of 0.11 MPa, and a compressive strength of 19.5 MPa.

[0267] Example 19

[0268] The consolidation plugging slurry was prepared according to the method of Example 13, except that the test conditions were changed from the sealed condition at 90°C to the sealed condition at 180°C, as follows:

[0269] According to the above method, the density of the plugging slurry at 25°C is 1.65g / cm 3 Under sealed conditions at 180°C, the plugging slurry took 10 minutes to gel and 0.5 hours to fully solidify. Using a testing device, the gel was flushed with water, and its mass retention was calculated to be 96.5%. After the gel fully solidified to form a plugging material, its compressive strength was tested to be 7 MPa, its lap shear strength was 0.12 MPa, and its compressive strength was 18.9 MPa.

[0270] Comparative Example 3

[0271] A plugging slurry was prepared according to the method of Example 13, except that the chemical consolidation material SMHD-1 was not added in step 3, that is, the chemical consolidation material SMHD-1 was 0. Under water erosion, the gel formed by the plugging slurry could not solidify to form a plug and could not achieve the plugging and pressure-bearing effect.

[0272] Comparative Example 4

[0273] A plugging slurry was prepared according to the method of Example 13, except that step 1 was not included, and no water-insoluble material was added in step 3, i.e., the amount of water-insoluble material was zero. The gel formed by this plugging slurry was easily diluted by water and easily washed away by flowing water. It also failed to solidify into a plug and could not provide a pressure-bearing plugging effect.

[0274] Examples 1-19 demonstrate that the gel formed by the plugging slurry prepared using the plugging composition of the present invention resists water dilution. After entering a flowing water layer, it can remain in the flowing water-containing layer and solidify over time under the formation's temperature and pressure, forming a solidified product with high compressive strength. This solidified product has a compressive strength exceeding 16 MPa, a mass retention rate exceeding 90%, and a pressure bearing capacity of up to 7 MPa. This solves the problem of leakage in flowing water-containing formations.

[0275] It can be seen from the results of the above embodiments and comparative examples that the embodiments of the present invention have significant advantages in terms of resistance to water dilution and high temperature resistance. When applied to flowing water layers, they have higher mass retention rate and compressive strength, and can be applied to water-containing formations with a temperature not exceeding 180°C, especially formations containing flowing water.

[0276] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.

Claims

1. A leak-proof composition, characterized in that: The plugging composition can be cross-linked to form a gel before or during injection into the formation, and the gel can be solidified at the leaking formation to form a plugging material; wherein, the mass retention rate of the gel after being flushed at a water flow rate of 10m / min at 50-180°C for 30 minutes is above 90%; the lap shear strength of the plugging material is 0.1-0.14MPa.

2. The leak-proof composition according to claim 1, wherein The bearing strength of the plugging material is not less than 7MPa.

3. The leak-proof composition according to claim 1 or 2, wherein The compressive strength of the plugging material is not less than 16 MPa, preferably 18-25 MPa.

4. The leak-proof composition according to any one of claims 1 to 3, wherein The lost circulation formation is a water-bearing formation, preferably a formation containing flowing water.

5. The leak-proof composition according to any one of claims 1 to 4, wherein The temperature of the leakage formation is 50-180°C.

6. The leak-proof composition according to any one of claims 1 to 5, wherein The plugging composition comprises the following components: a cross-linkable polymer, a cross-linking agent, a strengthening agent and a solvent; wherein the cross-linking agent comprises a metal cross-linking agent and / or an allyl cross-linking agent, and the strengthening agent is strengthening agent I and / or strengthening agent II; The enhancer I comprises a monomer represented by formula (I), dopamine and an initiator; Among them, R1, R2, R 21 and R 22 Each independently is hydrogen or C1-C 10 A straight or branched chain alkyl group; The reinforcing agent II includes a solidifying material and a solidifying retarder. The solidifying material is a material that can be hydrated and solidified when in contact with water. The compressive strength of the solidifying material is greater than 10 MPa, and the expansion rate is 0.5-1.5%.

7. The leak-proof composition according to claim 6, wherein: The cross-linkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the solvent is water. The leak-proof composition comprises the following components in parts by weight: 0.01-8 parts of a cross-linkable polymer, 0.01-8 parts of a metal cross-linking agent, 0.01-0.9 parts of an allyl cross-linking agent, 3-30 parts of a monomer represented by formula (I), 0.01-3 parts of dopamine, 0.01-8 parts of an initiator, and 100 parts of water. Preferably, the weight average molecular weight of the cross-linkable polymer is 2.5 million to 18 million g / mol, preferably 3 million to 16 million g / mol.

8. The leak-proof composition according to claim 7, wherein The metal cross-linking agent is selected from at least one of a zirconium cross-linking agent, a chromium cross-linking agent and an aluminum cross-linking agent; The allyl crosslinking agent is selected from at least one of N,N'-methylenebisacrylamide, glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate and ethoxylated pentaerythritol tetraacrylate.

9. The leak-proof composition according to claim 8, wherein The reinforcing agent I further comprises at least one of the monomers represented by formula (II), the monomers represented by formula (III), the monomers represented by formula (IV), the monomers represented by formula (V) and the monomers represented by formula (VI): Among them, R3, R4, R6, R7, R 11 、R 12 、R 13 、R 14 、R 15 、R 16 、R 18 、R 19 and R 20 Each independently is hydrogen or C1-C 10 A straight or branched alkyl group; R5 and R 17 Each independently is C1-C 20 straight chain or branched alkylene; R8, R9 and R 10 One of them is C1-C 20 The other two are independently hydrogen or C1-C 10 A straight or branched alkyl group, R' is C1-C 10 M1 and M2 are each independently H, Na, Li or K; X1 and X2 are each independently selected from Cl, Br or I; m is any integer from 4 to 20, and n is any integer from 3 to 10; Preferably, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (II) is 0.2-20 parts, preferably 2-15 parts; Preferably, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (III) is 0.5-20 parts, preferably 1-15 parts; Preferably, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (IV) is 0.2-5 parts, preferably 0.5-4 parts; Preferably, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (V) is 0.5-20 parts, preferably 1-15 parts; Preferably, based on 100 parts by weight of water, the weight portion of the monomer represented by formula (VI) is 0.5-10 parts, preferably 1-8 parts.

10. The leak-proof composition according to claim 6 or 7, wherein: The cross-linkable polymer is polyacrylamide and / or a polyacrylamide derivative, and the cross-linkable polymer exists in the form of a water-in-oil emulsion, and the water-in-oil emulsion comprises the cross-linkable polymer, oil, water and an emulsifier; Preferably, the weight proportions of the components in the plugging composition are as follows: 100 parts of water-in-oil emulsion, 0.01-8 parts of crosslinking agent, 3-30 parts of the monomer represented by formula (I), 0.01-2 parts of dopamine and 0.01-8 parts of initiator; Preferably, the mass ratio of the cross-linkable polymer, oil, water and emulsifier is 0.5-15:100:50-100:0.05-10, Preferably 1-10:100:60-90:0.1-5; Preferably, the oil is selected from at least one of waste white oil, waste diesel, waste engine oil and waste edible oil; Preferably, the cross-linkable polymer is anionic polyacrylamide, and the weight average molecular weight of the anionic polyacrylamide is 2.5-10 million g / mol, preferably 3-8 million g / mol; Preferably, the emulsifier is selected from at least one of octylphenol polyoxyethylene ether-10, octylphenol polyoxyethylene ether-15, nonylphenol polyoxyethylene ether-10, nonylphenol polyoxyethylene ether-15, Tween-20, Tween-60, Span-80, Span-85 and sodium dodecylbenzene sulfonate.

11. The leak-proof composition according to claim 10, wherein The reinforcing agent I further comprises at least one of the monomers represented by formula (II), the monomers represented by formula (III), the monomers represented by formula (IV), the monomers represented by formula (V) and the monomers represented by formula (VI): Among them, R3, R4, R6, R7, R 11 、R 12 、R 13 、R 14 、R 15 、R 16 、R 18 、R 19 and R 20 Each independently is hydrogen or C1-C 10 A straight or branched alkyl group; R5 and R 17 Each independently is C1-C 20 straight chain or branched alkylene; R8, R9 and R 10 One of them is C1-C 20 The other two are independently hydrogen or C1-C 10 A straight or branched alkyl group; R' is C1-C 10 A straight or branched alkylene group; M1 and M2 are each independently H, Na, Li or K; x is any integer from 4 to 20, and n is any integer from 3 to 10; Preferably, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (II) is 0.2-20 parts, preferably 2-15 parts; Preferably, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (III) is 0.5-20 parts, preferably 1-15 parts; Preferably, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (IV) is 0.2-5 parts, preferably 0.5-4 parts; Preferably, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (V) is 0.5-20 parts. Preferably 1-15 parts; Preferably, based on 100 parts by weight of the water-in-oil emulsion, the weight portion of the monomer represented by formula (VI) is 0.5-10 parts, preferably 1-8 parts.

12. The leak-proof composition according to claim 10 or 11, wherein The cross-linking agent is a mixture of an allyl cross-linking agent and an organometallic cross-linking agent, wherein the mass ratio of the allyl cross-linking agent to the organometallic cross-linking agent is 1:0.3-8, preferably 1:0.5-5; Preferably, the organometallic crosslinking agent is selected from at least one of an organozirconium crosslinking agent, an organochromium crosslinking agent, and an organoaluminum crosslinking agent.

13. The plugging composition according to any one of claims 1 to 12, wherein: The cross-linking agent further comprises a silicon cross-linking agent; Preferably, the silicon crosslinking agent is selected from at least one of water glass, ethyl silicate and γ-methacryloxypropyltrimethoxysilane; Preferably, the mass ratio of the allyl crosslinking agent, the metal crosslinking agent and the silicon crosslinking agent is 1:0.3-8:0.1-12, preferably 1:0.5-5:0.2-10.

14. The leak-proof composition according to any one of claims 1 to 13, wherein: The initiator is selected from at least one of potassium persulfate, ammonium persulfate, sodium persulfate, benzoyl peroxide, azobisisobutyramidine hydrochloride, di-tert-butyl peroxide, dodecyl peroxide, azobisisobutyronitrile and cumene hydroperoxide.

15. The leak-proof composition according to claim 6 or 7, wherein: The plugging composition further comprises a salt-resistant polymer, which together with the cross-linkable polymer constitutes a water-indispersible material; the weight proportions of the components in the plugging composition are as follows: 10-15 parts of the water-indispersible material, 0.1-4 parts of the cross-linking agent, 50-200 parts of the consolidating material, 0.5-5 parts of the retarder, and 100 parts of water; Preferably, the mass ratio of the salt-resistant polymer to the cross-linkable polymer is 10:0.5-3; Preferably, the cross-linkable polymer is polyacrylamide and / or a polyacrylamide derivative; Preferably, the weight average molecular weight of the cross-linkable polymer is 2 million to 14 million g / mol, preferably 5 million to 14 million g / mol; Preferably, the solid retarder is selected from 2-acrylamide-2-methylpropanesulfonic acid polymer and / or hydroxycarboxylic acid polymer.

16. The plugging composition according to any one of claims 1 to 15, wherein: The density of the plugging composition after mixing at 25°C is 1-2 g / cm 3 , preferably 1.2-1.65g / cm 3 .

17. A plugging material, characterized in that: The plugging material is obtained by curing the plugging composition according to any one of claims 1 to 16.

18. The plugging material according to claim 17, wherein: The curing temperature is 50-180°C; And / or, the compressive strength of the plugging material is 15-25 MPa.

19. Use of the plugging composition according to any one of claims 1 to 16 or the plugging material according to claim 17 or 18 in plugging oil well formations; preferably, the oil well formation is an oil well formation containing flowing water at a temperature of 50-180°C.

20. A method for plugging leaks in oil wells, characterized in that: The method comprises directly injecting the plugging composition described in any one of claims 1 to 16 into the fractures of an oil well formation so that the plugging composition forms a gel during the injection into the formation, or injecting the plugging composition described in any one of claims 1 to 16 into the fractures of an oil well formation after forming a gel, wherein under formation conditions, the gel solidifies at the leakage formation to form a plugging material; wherein the mass retention rate of the gel after being flushed for 30 minutes at a water flow rate of 10 m / min at 50-180° C. is above 90%; and the lap shear strength of the plugging material is 0.1-0.14 MPa.

Citation Information

Patent Citations

  • Plugging agent composition, plugging agent and preparation method and application of the plugging agent

    CN110734754A

  • Composite gel leaking stoppage material and composite gel leaking stoppage slurry

    CN112280543A